Clinical efficacy of laparoscopic radical cystectomy with intracorporeal urinary diversion and an analysis of factors influencing complications - Fang, Hongzhi; Ji, Huihua; Shi, Changjian; Zhou, Benrui; Xu, Jie; Luo, Yuli; Li, Yunfei (Frontiers in Oncology, 2025)
PurposeTo explore the feasibility of combined laparoscopic radical cystectomy (LRC) and intracorporeal urinary diversion (ICUD) in the treatment of bladder cancer, as well as the influencing factors related to complications.MethodsA retrospective study was conducted on 116 bladder cancer patients who underwent LRC at our facility between January 2019 and December 2023. Based on the different urinary diversion methods, 78 patients received extracorporeal urinary diversion (ECUD), while 38 patients underwent intracorporeal urinary diversion (ICUD). The two groups were compared in terms of clinicopathologic data, perioperative outcomes, postoperative tumor control, complication rates, and their influencing factors.ResultsNo statistically significant differences were observed between the two groups in terms of median total operative time, hospital stay, perioperative transfusion rate, and short-term oncological outcomes. Compared to the ECUD group, the ICUD group experienced less intraoperative blood loss (200 ml vs. 350 ml) and an earlier start to postoperative liquid diet intake (4 days vs. 5 days) (p < 0.05). A total of 24 cases of ≥III grade complications occurred within 90 days postoperatively, with 20 cases in the ECUD group and 4 in the ICUD group. There was no significant difference in the incidence of ≥III grade complications between the two groups (p > 0.05). Sepsis was the most common major complication. Logistic regression analysis identified smoking history, diabetes, and intraoperative blood loss as independent risk factors for ≥III complications.ConclusionsICUD is a secure and effective method with advantages such as improved postoperative bowel recovery, reduced intraoperative blood loss, and fewer overall postoperative complications. Furthermore, major complications are influenced by multiple risk factors and should be carefully considered during preoperative and postoperative management.